STRATEGI METAKOGNISI MENULIS TEKS BERITA SISWA SMP IT INSAN KAMIL HALMAHERA SELATAN - Ismail, Julia; La Ode Alumu, Wa Ode Murima; gay, masayu (Program Studi Pendidikan Ekonomi Institut Sain dan Kependidikan (ISDIK) Kie Raha Maluku Utara, 2025)
Learning to write news texts often leaves problems in the form of quality. Writing still seems like a mechanistic activity, not an activity that involves high critical and reflective thinking. This study aims to reveal students' metacognitive strategies in writing news texts. The problems studied are metacognitive strategies and the ability to apply metacognitive strategies. The study was conducted on students of class VIII of SMP IT Insan Kamil Halmahera Selatan qualitatively descriptively and exploratively with data collection techniques, namely questionnaires, interviews, and documentation. The results of the study showed that the metacognitive strategies, namely planning, monitoring, and evaluation obtained an average score of 4.15, classified as